Development of an obeche wood allergen quantification assay for the assessment of allergen exposure in workplaces - Kespohl, Sabine; Sander, Ingrid; Schulze, Johannes; Poppe, Marnix; Brüning, Thomas; Raulf-Heimsoth, Monika (Scandinavian Journal of Work, Environment & Health, 2008)
' ' OBJECTIVES ': 'The purpose of this study was to develop a quantification assay to measure airborne concentrations of obeche wood allergen at workplaces. ' ' METHODS ': 'Specific polyclonal antibodies to obeche wood were produced in rabbit and used to develop an inhibition enzyme immunoassay (EIA). Inhalable dust samples from three wood-processing companies were taken with a stationary sampling device (Gravicon VC25). The loaded dust filters were extracted under standardized conditions and measured with the assay. In addition, the antigen and allergen contents of obeche wood from different sources (Cameroon, N=5; Ghana, N=4) were analyzed from immunoblots, detected with rabbit immunoglobulin (Ig) G and human Ig E. ' ' RESULTS ': 'Polyclonal antibodies specific for obeche wood allergens, without cross-reactivity to other woods, were used to establish the inhibition enzyme immunoassay. The assay is able to quantify allergen concentrations from 30 to 300 ng/ml. With inhibition enzyme immunoassay, exposure to airborne obeche wood allergen can be monitored in wood-processing companies. Inhalable dust samples from workplaces contained an average allergen concentration of 15 µg/g dust. Significantly lower protein and allergen contents were measured for obeche wood from Cameroon (ayous) in one company. IgE immunoblots indicated that the lower antigen and allergen contents of the ayous wood may be the result of its lacking the major obeche wood allergen, Trip s 1. ' ' CONCLUSIONS ': 'The data showed that the total dust concentration in workplaces containing obeche wood dust did not correspond to the assessed allergen concentration. To estimate exposure limits regarding sensitization risk, it is necessary to measure the allergen content directly.
Keywords: aeroallergens; allergen; allergen exposure; assessment; exposure assessment; obeche wood allergen; occupational allergy; quantification assay; wood allergen; wood dust exposure; workplace